Metabolic syndrome in urban and rural communities of Bangladesh - Billah, Syed Muhammad Baqui; Jahan, MS (International Journal of Human and Health Sciences (IJHHS), 2018)
Background: Metabolic syndrome (MetS) is a rising public health concern. Bangladesh profile need exploration through research. Methods: Socio-epidemiologic factors of 341 urban and 149 rural people were studied with anthropometric examination, blood pressure recording and fasting blood for sugar (FBS), triglyceride (TG) and high density lipoprotein (HDL) analysis. MetS was decided on the basis of National Cholesterol Education Program ATP III criteria. Result: Prevalence of MetS was 38.78% (95% CI: 34.56%-43.16%). Rural prevalence (48.99%; 95% CI: 41.09%-56.94%) was more (p=0.002) than urban (34.31%; 95% CI: 29.47%-39.50%); low HDL cholesterol prevailed around 97% urban and 93% rural respondents; high TG was found among 48% urban and 59% rural respondents (p=0.02), 21% urban and 44% rural respondents were obese (p<0.001); around 15% urban and 22% rural had hypertension (HTN, p=0.04); high FBS was found among 28% urban and 26% rural respondents. Age (OR=1.06, 95% CI: 1.04-1.09) and exercise (OR=2.31, 95% CI: 1.40-3.80) of urban area whereas only males of rural (OR=5.88, 95% CI: 2.52- 13.73) area were significantly associated with MetS. Conclusions: Prevalence of MetS is higher in rural Bangladesh than urban in terms of dyslipidaemia, HTN and obesity. Health education and mass campaign regarding the risk factors including change in lifestyle can modify the condition. International Journal of Human and Health Sciences Vol. 02 No. 02 April’18. Page : 71-77